Pragmaticistic Echoes in T. Kuhn: For a Peircean Reinterpretation of “The Structure of Scientific Revolutions” (Nóema, 2022)
Does The structure of scientific revolutions still provide a meaningful contribution to philosophical praxis, half a century after its first publication? In this article, a pragmaticistic read of Kuhn's text is provided through the Peircean concepts of Habit, Abduction and Truth, which reopen a prolific comparison between the two philosophers, still overlooked to these days.
Keywords: Thomas Kuhn; Charles Sanders Peirce; habit; abduction; paradigm; progress; scientific revolutions